2013
DOI: 10.4102/curationis.v36i1.106
|View full text |Cite
|
Sign up to set email alerts
|

A report on the development and implementation of a preceptorship training programme for registered nurses

Abstract: Background: Clinical supervision represents an important aspect in the development of nursing students’ clinical skills. At the School of Nursing (SoN) the clinical supervisors employed by the University of the Western Cape (UWC) have limited contact sessions with students in the clinical setting. However, with the increase in student numbers a need was identified to strengthen the support given to nursing students in the service setting.Objective: A preceptorship training programme for nurses was developed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…The reported benefits from participating in the CPD course, that is, increased ability to give collegial support; increased trust in one’s abilities; increased emphasis on reflection; and increased professional status may be explained by a course targeting the needs of preceptors as its development was guided by input not only from preceptors but also service providers. This confirms the findings from a study by Jeggels et al [ 20 ] who concluded that collaborative partnerships are imperative to the success of preceptorship education. Hilli et al [ 6 ] argue that a supportive environment is fundamental for both preceptors and students.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reported benefits from participating in the CPD course, that is, increased ability to give collegial support; increased trust in one’s abilities; increased emphasis on reflection; and increased professional status may be explained by a course targeting the needs of preceptors as its development was guided by input not only from preceptors but also service providers. This confirms the findings from a study by Jeggels et al [ 20 ] who concluded that collaborative partnerships are imperative to the success of preceptorship education. Hilli et al [ 6 ] argue that a supportive environment is fundamental for both preceptors and students.…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion, the literature seems to underline the importance of preceptor education [ 10 , 16 , 17 ]. Even though, the course content seems to share some commonalities, for example, adult learning principles, communication skills and feedback strategies, the educational programmes seem to differ considerably in duration; from two hour courses [ 18 ], one to two days’ workshops [ 3 , 10 , 19 ] to a two week long course [ 20 ], and few courses are presented as continuous professional development meriting academic credits. The aim of the current study was to evaluate preceptors’ experiences of preceptorship in clinical practice after completion of a credit bearing continuous professional development (CPD) course on advanced level.…”
Section: Introductionmentioning
confidence: 99%
“…These age ranges may be considered acceptable considering the average age of graduates in Caliskan and Ergun’s ( 2012 ) study was 24.05 years. It was also below the average age of those that were reported to be studying for the degree in nursing in Western Cape (Jeggels, Traut & Africa 2013 ). The greater number of women (76.6%; n = 82) suggests a dominance of women for nursing, as confirmed by Dyess and Sherman ( 2009 ) and by Caliskan and Ergun ( 2012 ) in their study on graduate nurses.…”
Section: Discussionmentioning
confidence: 84%
“…The school is the largest residential nursing school in South Africa and has been offering the Bachelor of Nursing (B Nursing) degree as its core undergraduate programme since 2004 ( Jeggels, Traut & Africa 2013 :2). The school positions itself as an innovative School of Nursing and Midwifery in the country and advocates a community-, problem- and competency-based curriculum.…”
Section: Research Methods and Designmentioning
confidence: 99%